Incidence and Characteristics of Nosocomial Influenza at an Academic Medical Center. (October 2020) - Azim, Ahmed Abdul; Schrank, Gregory; Feeser, Baevin; Wright, Sharon
Abstract : Background: Despite introduction of mandatory vaccination of healthcare workers (HCWs) in 2011, we continued to see occasional cases of nosocomial influenza. We sought to understand the characteristics of patients who acquired nosocomial influenza to better target prevention efforts. Methods: The study population was a retrospective cohort of all patients aged ≥18 years admitted to an academic medical center between September 2012 and August 2018. Patient data obtained included age, admission/discharge date, service line, influenza vaccination status on admission, and virus serotype. Nosocomial influenza was defined as positive polymerase chain reaction (PCR) or antigen testing for influenza A/B >3 days after admission. Each influenza season, patients with nosocomial influenza or community-acquired influenza (CA-I) were censored after the positive test. Means with standard deviations are reported (SAS version 9.4). Results: Overall, 223, 005 patient admissions occurred during the study period: 222, 154 (99.6%) were without confirmed influenza infection, 788 (0.35%) had CA-I, and 63 (0.03%) had nosocomial influenza (Fig. 1). The mean age of patients without influenza infection was 57.6 ± 19.3 years compared to 66.5 ± 18.8 years for those with CA-I and 67.1 ± 13.5 with nosocomial influenza. Influenza A accounted for 630 cases (80%) of CA-I, and 58 cases (92%) of nosocomial influenza. Also, 31 (48%) with nosocomial influenza had been vaccinated against influenza prior to admission (Table 1). Most nosocomial influenza cases (78%) occurred on medicine and oncology units. Conclusions: Influenza A represented a larger percentage of nosocomial influenza compared to CA-I. The proportion of nosocomial influenza cases remained stable during the study period, even after introduction of PCR tests in the 2014–2015 season. The mean age of the nosocomial influenza group was greater compared to the CA-I and no influenza groups. More than half of nosocomial influenza cases were unvaccinated at the time of admission, demonstrating the importance of improving vaccine uptake among vulnerable populations. Funding: None Disclosures: None